1998
DOI: 10.1111/j.1600-0609.1998.tb01104.x
|View full text |Cite
|
Sign up to set email alerts
|

Approaches towards successful home treatment in patients with inhibitors

Abstract: Significant advances have been achieved in prevention of haemophilic disability through prophylactic administration of concentrates and early administration of coagulation factors to control new bleeding episodes, but there is only limited experience with home treatment in haemophilia patients with inhibitors. A home treatment programme using recombinant activated factor VII (rFVIIa; NovoSeven®, Novo Nordisk, Bagsværd, Denmark) in early intervention against minor bleeds in patients with high responding inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 1 publication
(1 reference statement)
0
8
0
Order By: Relevance
“…However, the time period investigated in most studies are comparably short [22–26] and our study is the first to show that the safety using bypassing products at home is very good also over an extended time period such as 7.5 years.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…However, the time period investigated in most studies are comparably short [22–26] and our study is the first to show that the safety using bypassing products at home is very good also over an extended time period such as 7.5 years.…”
Section: Discussionmentioning
confidence: 85%
“…To date, studies and reports on bypassing products in home treatment have primarily been focusing on the efficacy in a shorter time perspective and have not been evaluating the feasibility, efficacy and safety of the treatment for a long time period [20–26].…”
Section: Introductionmentioning
confidence: 99%
“…Self‐management initiatives for haemophilia have focused mainly on self‐administration of clotting factor concentrates , which is vitally important because clotting factor treatment is the key to effective haemophilia management. Physical activity is also important, for physiotherapy was associated with reduced pain and improved functional ability , and exercise programmes designed specifically for people with bleeding disorders led to improvements in joint motion, strength and walking ability .…”
Section: Self‐management Of Chronic Joint Painmentioning
confidence: 99%
“…Reason for exclusion Zwahlen and Beck [33] Efficacy not reported Sjamsoedin et al [31] No (separate) evaluation of non-surgical joint bleeds in inhibitor patients Macik et al [34] Not enough information on dosage, frequency or timing Lindley et al [35] Efficacy not reported Schmidt et al [36] No (separate) evaluation of non-surgical joint bleeds in inhibitor patients Lusher [37] No (separate) evaluation of non-surgical joint bleeds in inhibitor patients McPherson et al [38] No (separate) evaluation of non-surgical joint bleeds in inhibitor patients Rice and Savidge [39] No (separate) evaluation of non-surgical joint bleeds in inhibitor patients DiMichelle [40] No clinical study Hay et al [41] Not enough information on dosage, frequency or timing Arkin et al [42] No (separate) evaluation of non-surgical joint bleeds in inhibitor patients Ingerslev et al [43] Efficacy not reported Ingerslev et al [44] Not enough information on dosage, frequency or timing Lusher [45] No clinical study Lusher et al [46] No clinical study Mauser-Bunschoten et al [47] No bolus infusion Petrini and Klementz [48] No clinical study Shapiro et al [49] No (separate) evaluation of non-surgical joint bleeds in inhibitor patients Scharrer [50] No (separate) evaluation of non-surgical joint bleeds in inhibitor patients Brackmann et al [51] Efficacy not reported Liebman et al [52] No (separate) evaluation of non-surgical joint bleeds in inhibitor patients Lusher [53] No clinical study Negrier and Lienhart [54] No clinical study Berrettini et al [55] Efficacy not reported Friederich et al [56] No (separate) evaluation of non-surgical joint bleeds in inhibitor patients Hedner [57] No clinical study Santagostino et al [58] No bolus infusion Shirahata et al [27] Not enough information on dosage, frequency or timing Smith et al [59] No (separate) evaluation of non-surgical joint bleeds in inhibitor patients Levi…”
Section: Appendix 2: Excluded Studies With Reasonsmentioning
confidence: 99%